Family size and construct of the early adolescent's emotional intelligence - Naghavi, Fataneh; Redzuan, Ma'rof (Marsland Press, 2012)
Emotional intelligence is a set of abilities that include conception, emotion appraisal and expression, emotion management and regulation. The emotional intelligence structure is a concept with little empirical research, particularly in relation to the link between family environment and personality characters and with respect to family members of early adolescents. For this reason, the specific objective of this research is to determine the relationship between family size and early adolescent’s emotional intelligence. The present research was carried out among 234 Iranian students in the second and grades of guidance schools (age 12-15) in Tehran, Iran. The students (girls and boys) were clustered through random and multistage sampling. Data were collected using the family background questionnaire and Schutte’s (1998) Emotional Intelligence Scale. Results of multiple comparisons of LSD indicate that there is significant difference between groups of family size. Consequently, multi comparisons of LSD confirmed the results of the ANOVA. The findings indicate that the early adolescents, whose families have less members, have higher emotional intelligence.